External shocks and international inflation linkages: a global VAR analysis - Alessandro Galesi; Marco J. Lombardi (European Central Bank (ECB), 2009)
Amid the recent commodity price gyrations, policy makers have become increasingly concerned in assessing to what extent oil and food price shocks transmit to the inflationary outlook and the real economy. In this paper, we try to tackle this issue by means of a Global Vector Autoregressive (GVAR) model. We first examine the short-run inflationary effects of oil and food price shocks on a given set of countries. Secondly, we assess the importance of inflation linkages among countries, by dis-entangling the geographical sources of inflationary pressures for each region. Generalized impulse response functions reveal that the direct inflationary effects of oil price shocks affect mostly developed countries while less sizeable effects are observed for emerging economies. Food price increases also have significative inflationary direct effects, but especially for emerging economies. Moreover, significant second-round effects are observed in some countries. Generalized forecast error variance decompositions indicate that considerable linkages through which inflationary pressures spill over exist among regions. In addition, a considerable part of the observed headline inflation rises is attributable to foreign sources for the vast majority of the regions.
Keywords: C32; E31; 330; commodity prices; Global VAR; inflation; oil shock; second-round effects; Ölpreis; Rohstoffpreis; Inflation; Inflationskonvergenz; VAR-Modell; Industrieländer; Schwellenländer